Sensemaking at work: How rationalized knowledge hiding and communication patterns affect decision quality - Zhihao Gao; Muhammad Waseem Bari; Sadia Shaheen (PLoS ONE, 2026)
This paper employs sensemaking theory to examine the relationships between rationalized knowledge hiding, communication patterns, and the quality of decision-making in information technology firms. Additionally, this study operationalized sensemaking processes as a mediator in the above mentioned relationships. The study employed a three-time lag approach with a 45-day gap, utilizing data from 348 managers, supervisors, and leaders. Partial least squares structural equation modeling and SmartPLS 4 are employed for the analyses. The results indicate that rationalized knowledge-hiding and communication patterns have a significant impact on decision-making quality. Moreover, sensemaking processes partially/complementary mediate the relationship between rationalized knowledge hiding, communication patterns, and decision-making quality. Incorporating sensemaking processes into the study model provides deeper insight into managers’ decisions and maps the temporal nature of these relationships. These valuable findings shed light on new meanings and directions for theoretical perspectives and their relevance in management and organizational behavior.